Ultrafast Channel II process induced by a 3-D texture with enhanced acceptor order ranges for high-performance non-fullerene polymer solar cells. Issue 9 (2nd July 2018) - Chen, Shanshan; Lee, Sang Myeon; Xu, Jianqiu; Lee, Jungho; Lee, Kyu Cheol; Hou, Tianyu; Yang, Yankang; Jeong, Mingyu; Lee, Byongkyu; Cho, Yongjoon; Jung, Sungwoo; Oh, Jiyeon; et al.
Abstract : The enhanced SMA order ranges in well-intermixed 3-D textures enabled an ultrafast Channel II process, affording a highest efficiency of 12.01%. Abstract : To achieve efficient non-fullerene polymer solar cells (NF-PSCs), an in-depth understanding of the key properties that govern the power output is necessary. Herein, three trialkylsilyl substituted benzodithiophene-based polymer donors (PJ1, PJ2, and PJ3) were synthesized with fine-tuning of the highest occupied molecular orbital (HOMO)/lowest unoccupied molecular orbital (LUMO) and optical absorption. Using the polymer series paired with absorption-complementary small molecular acceptors (SMAs), namely, m -ITIC, IDIC, and AIDIC, we systematically studied the performance of a 3 × 3 matrix of NF-PSCs. An increasing open-circuit voltage with deepening HOMOs of the polymer donors, and the enhanced short-circuit current ( J SC ) and fill factor (FF) were ascribed to the well-intermixed blend morphology containing enhanced SMA order ranges with mixed face-on and edge-on orientations, the so-called 3-D texture. Such an optimal microstructure is best exemplified in the PJ2:IDIC combination, affording a highest efficiency of 12.01% with a simultaneously high J SC of 17.0 mA cm −2 and FF of 75.3%. The devices with an active layer thickness of 300 nm still maintain an impressive efficiency approaching 10% with a decent FF of 60.0%. Moreover, the Channel II process, i.e., photoinduced hole transfer through acceptor excitation, was demonstrated to be crucially important for photocurrent generation. This study highlights the importance of optimizing the trade-off between charge separation/transport and domain size to achieve high-performance NF-PSCs.